Treatment stability of valproate, carbamazepine, and levetiracetam: a therapeutic drug monitoring study - Lucia Žigová; Mária Göböová; Orsolya Hrubá; Andrea Gažová; Stanislava Kosírová (Pharmacia, 2025)
This study evaluated treatment stability–defined as the maintenance of therapeutic serum concentrations–of antiepileptic drugs in patients undergoing long-term therapy, with emphasis on the role of therapeutic drug monitoring in optimizing pharmacotherapy. A retrospective analysis of 78 patients at the University Hospital in Nitra (2020–2022) examined serum drug concentrations and treatment stability for valproate, carbamazepine, and levetiracetam. Psychiatric diagnoses were highly prevalent among patients using valproate (93.18%) and carbamazepine (61.10%), whereas levetiracetam was primarily prescribed for neurological conditions (60%). The proportion of patients with therapeutic serum concentrations increased from the first to the second measurement for all drugs, with carbamazepine demonstrating the most substantial improvement (66.7% to 100%). Treatment stability was highest among patients receiving carbamazepine (66.7%), compared to those on valproate (34.1%) and levetiracetam (31.3%). Outpatient status and carbamazepine use were significantly associated with greater treatment stability, underscoring the importance of patient setting and drug selection in optimizing antiepileptic therapy.